IDENTIFIABILITY AND IDENTIFICATION OF THE AIRCRAFT LONGITUDINAL MOTION WITH THE MAXIMUM LIKELIHOOD METHOD - Tunik, А.А.; Klipa, А.M. (Proceedings of National Aviation University (archive), 2005)
The peculiarities of the identification problem of the longitudinal motion of one aircraft class according to flight test records in the presence of intensive noises are considered. It is shown, that for the given aircraft class with the given input signals only identification of the short period component of the longitudinal motion is possible. The identification of the short period motion of aircraft using the maximum likelihood method is executed.